Carcinoma with Vertebral Column Metastasis in Two Dogs - de Cristo, Thierry Grima; de Noronha, Laura Formighieri; Biezus, Giovana; Cerqueira, Cinthya dos Santos; Fernandes, Natália Coelho Couto de Azevedo; Bonatto, Gustavo Ribeiro; Arruda, Iliane Perin; Casagrande, Renata Assis (Acta Scientiae Veterinariae, 2020)
Background: Carcinomas are aggressive and invasive malignancies that originate from any type of epithelial cell and are responsible for many deaths in dogs. Carcinoma metastases occur primarily via the lymphatic route; however, they can occur by blood flow, thus reaching bone structures. In dogs, metastasis of mammary and squamous cell carcinomas to the skeletal system is poorly described. The aim of this study was to report two cases of dogs that developed metastases of carcinomas to the vertebral column. Cases: Case 1. A 10 years-old, male, mixed-breed dog with paralysis of the left pelvic limb, subcutaneous mass in the lumbar region, apathy, anorexia and progressive weight loss and with a previous history of amputation of the right pelvic limb resulting from squamous cell carcinoma (SCC) in the integument of the cranial face of the femorotibiopatellar joint. Due to the patient’s clinical condition and the negative prognosis associated with the neoplasia, euthanasia was performed. At necropsy, infiltrating the lumbar vertebrae from L5 to L7, a whitish and firm mass of approximately 15 x 8 cm was observed. Histologically, it comprised a malignant epithelial neoplastic development consisting of nests and cords interspersed with fibrovascular stroma, containing multiple keratine pearls. There was moderate to severe anisocytosis, severe anisokariosis, and about 4 mitosis figures for every 10 high power fields (400x). The histological features were consistent with an invasive SCC. Anti-cytokeratin and anti-p63 immunohistochemical (IHC) evaluations were performed, both with immunoreactivity in neoplastic cells. Case 2. An 8 years-old, female, Chihuahua with bilateral paralysis of the pelvic limbs, anorexia, and progressive weight loss, with a history of excision of solid mammary carcinoma. The clinical condition evolved to the absence of deep pain in all limbs and fecal and urinary retention, opting for euthanasia. At necropsy, a nodule between T3 and T4 was observed, yellowish-white and firm, measuring about 5 x 3.8 cm, invading the spinal canal, and compressing the spinal cord. Histologically, it comprised malignant epithelial neoplasia infiltrating intervertebral ligaments, musculature, and vertebrae of the thoracic spine, organized in a dense mantle of polygonal to rounded cells, delimited in lobes by abundant fibrovascular tissue. Moderate anisokaryosis and accentuated anisocytosis were observed and about 6 mitosis figures for every 10 high power fields (400x). The histological characteristics of the tumor were compatible with metastasis due to grade II solid mammary carcinoma. Immunohistochemical evaluations of anti-cytokeratin, anti-c-erbB2, and anti-estrogen and progesterone receptors were performed, with immunoreactivity for cytokeratin and c-erbB2 in neoplastic cells. Discussion: There are no current data indicating which tumors that metastasize most frequently to the vertebral column. In the reported cases, it was found that the clinical signs presented by the animals are directly associated with the compression of specific areas of the spinal cord, as well as bone pain, resulting from tumor expansion and degeneration of the bone matrix, similar to what has been reported previously. The immunohistochemical diagnosis of anti-p63 in case 1 and anti-oncoprotein C-erbB2 in case 2, were essential to determine the neoplastic origin in the absence of the primary tumor. Despite being a place of low incidence of metastases, bones have a physiologically favorable environment for the implantation of neoplastic cells, especially when there is bone marrow involvement. Because of this and despite the rare occurrence, metastasis of carcinomas to the vertebral column should always be considered as differential diagnoses in patients presenting with clinical signs compatible with spinal cord compression and a history of previous neoplasia.